Just the other side of the coin? From error to insight analysis. (October 2016) - Smuc, Michael
To shed more light on data explorers dealing with complex information visualizations in real-world scenarios, new methodologies and models are needed which overcome existing explanatory gaps. Therefore, a novel model to analyze users' errors and insights is outlined that is derived from Rasmussen's model on different levels of cognitive processing, and integrates explorers' skills, schemes, and knowledge (skill–rule–knowledge model). After locating this model in the landscape of theories for visual analytics, the main building blocks of the model, where three cognitive processing levels are interlinked, are described in detail. A case study illustrates how the cognitive processing efforts can be identified from triangulated eye-tracking and think-aloud data. Finally, the model's applicability, challenges in measurement, and future research options are discussed.